Direct oral anti-Xa anticoagulants versus warfarin in newly diagnosed atrial fibrillation and CKD: the Korean National Health Insurance Data - Kee, Youn Kyung; Jeon, Hee Jung; Oh, Jieun; Yoo, Tae-Hyun; Kang, Dongwoo; Lee, Jungkuk; Shin, Dong Ho (Frontiers in Medicine, 2023)
Introduction Despite the benefits of direct oral anti-Xa anticoagulants (DOACs), the risk–benefit profile of DOAC therapy compared to warfarin therapy in patients with non-valvular atrial fibrillation (AF) and chronic kidney disease (CKD), including end-stage renal disease (ESRD), is uncertain. Methods We conducted a retrospective study using the Korea National Health Insurance Database from 2013 to 2018. We evaluated patients with incident non-valvular AF and CKD. The primary and secondary effectiveness outcomes were ischemic stroke and all-cause mortality. The primary safety outcomes included intracranial hemorrhage, gastrointestinal bleeding, and extracranial or unclassified major bleeding. Results Among the 1,885 patients evaluated, 970 (51.5%) initiated warfarin therapy, and 915 (48.5%) initiated DOAC therapy. During a mean follow-up period of 23.8 months, there were 293 and 214 cases of ischemic stroke and all-cause death, respectively. Kaplan–Meier survival analysis showed significantly lower all-cause mortality in DOAC users than in warfarin users. In multivariate Cox regression analyses, DOAC therapy had a hazard ratio for all-cause mortality of 0.41 (95% CI, 0.30–0.56; p < 0.001) compared to warfarin therapy. Additionally, DOAC therapy significantly reduced intracranial hemorrhage and gastrointestinal bleeding. Discussion Our study demonstrates that DOAC therapy has a better risk–benefit profile than warfarin therapy in patients with AF and CKD. Further well-designed clinical trials are needed to clarify the benefits of DOACs in this patient population.